Macro Effects of Corporate Restructuring in Japan - Kim, Se-Jik (IMF Working Papers; Working Paper ;, 2003)
This paper presents a framework for quantitatively evaluating the macroeconomic effects of corporate restructuring and applies it to Japan. Using firm-level financial statement data, it estimates total factor productivity (TFP) of individual Japanese firms. Given the estimated distribution of productivity across firms, the paper simulates the effect of optimal restructuring, that is, reallocation of resources from less-productive firms to more-productive ones, on the dynamic path of aggregate output. The results show that the benefits of restructuring could substantially exceed the costs.